Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Ekonomi - Helena Rosalia Parera (Program Studi Pendidikan Ekonomi, Universitas Flores, 2018)
This study aims to determine the effect of emotional intelligence on economic learning outcomes. The results showed that there was a significant effect of emotional intelligence on economic learning outcomes in the amount of t = 1.991 and sig. 0.047 < 0.005. These findings reveal that emotional intelligence has a significant influence in improving students economic learning outcomes. From these finding it is expected that the school does not only produce student who have intellectual intelligence but must have emotional intelligence.